2021
DOI: 10.1002/anie.202100431
|View full text |Cite
|
Sign up to set email alerts
|

Titanium‐Catalyzed Intermolecular Hydroaminoalkylation of Alkenes with Tertiary Amines

Abstract: The first cationic titanium catalyst system for the intermolecular hydroaminoalkylation of alkenes with various tertiary alkylamines is presented. Corresponding reactions which involve the addition of the a-CÀH bond of a tertiary amine across the CÀC double bond of an alkene take place at temperatures close to room temperature with excellent regioselectivity to deliver the branched products exclusively. Interestingly, for selected amines, a-C À H bond activation occurs not only at N-methyl but also at N-methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 40 publications
(2 reference statements)
1
24
0
Order By: Relevance
“…The latter result deserves particular attention because trimethylamine is a side product of the industrial production of methylamine and dimethylamine and according to the literature, [16] a lack of need for trimethylamine exists in the chemical industry because its conversion into useful products is difficult to achieve. With regard to substrate scope it must be mentioned that we did not observe any product formation with N , N ‐dimethylaniline, which is consistent with our previous observation that tertiary arylamines, do not undergo hydroaminoalkylation with alkenes in the presence of TiBn 4 and Ph 3 C[B(C 6 F 5 ) 4 ] [10f] …”
Section: Resultssupporting
confidence: 90%
“…The latter result deserves particular attention because trimethylamine is a side product of the industrial production of methylamine and dimethylamine and according to the literature, [16] a lack of need for trimethylamine exists in the chemical industry because its conversion into useful products is difficult to achieve. With regard to substrate scope it must be mentioned that we did not observe any product formation with N , N ‐dimethylaniline, which is consistent with our previous observation that tertiary arylamines, do not undergo hydroaminoalkylation with alkenes in the presence of TiBn 4 and Ph 3 C[B(C 6 F 5 ) 4 ] [10f] …”
Section: Resultssupporting
confidence: 90%
“…Perhaps the most attractive and atom-economical approach for the construction of α-alkylated amines is the net insertion of an alkene into an amine α-C–H bond, often termed a hydroamino­alkylation (HAA) reaction . For secondary and tertiary amines, the catalytic HAA of non-electrophilic alkenes has been dominated by early transition-metal-based catalysts. These reactions are typically sensitive to the substitution α to nitrogen, with the majority of reports focusing on N -methyl group functionalization, and linear selectivity being a particular challenge .…”
Section: Introductionmentioning
confidence: 99%
“…After hydrochloride formation, we were able to unambiguously determine the structure of 5 b•HCl by single crystal X-ray diffraction (Figure 1). [16] Additional hydroaminoalkylation reactions performed with N-methylpyrrolidine (1 c) and various alkenes (2 a-d) then revealed that 1 c behaves similar but unfortunately, we were not able to seperate the two hydroaminoalkylation products which were formed in all theses reactions. However, corresponding product mixtures could be isolated in yields of 18-36 % and GC-analyses showed that again alkylation at the a-CH 2 -group of the heterocyclic ring is slightly favored.…”
Section: Angewandte Chemiementioning
confidence: 89%
“…Ellipsoids are drawn at the 50 % probability level. [16] Scheme 3. Multigram scale hydroaminoalkylation of 1-dodecene (2 d) with N-methylpiperidine (1 a).…”
Section: Angewandte Chemiementioning
confidence: 99%
See 1 more Smart Citation